COMMUNICATION PATTERNS OF CAREGIVERS IN FOSTERING STUDENT ORGANIZATIONS AT AS-SHOFA BOARDING SCHOOL IN - Rahmat Hidayat (Indonesian Journal of Islamic Communication, 2024)
Islamic boarding schools in their function as educational and cadre institutions have a role to prepare cadres who will take part and build society towards religious life, nation and state. As-Shofa Jubung Islamic Boarding School began to apply management science in management, so that there began to be quite good developments in the pattern of education and its results. Mudabbir or boarding school administrators always foster, assist, and direct students towards the good and right direction. So this role is very important and vital. In addition, the board of Pondok Pesantren has a management role in managing the management structure in Pondok Pesantren, both in terms of programs, organizing, controlling, and evaluating. How is Communication in the Initial Development of Santri Organization in As-Shofa Jubung Jember Islamic Boarding School? 2. How is Communication in the Active Development of Santri Organization in As-Shofa Jubung Jember Boarding School? 3. How is Communication in the Final Development of Santri Organization in As-Shofa Jubung Jember Islamic Boarding School? This research approach is qualitative with the type of case study. Data acquisition using observation, interviews and documentation which are then analyzed using four stages, namely: data collection, data condensation, data presentation, conclusion drawing or verification. The result of this research is that the communication pattern in the coaching of the santri organization at the As-Shofa Jubung boarding school varies according to the stage of coaching carried out. In the initial coaching stage, chain communication patterns are applied in leadership and management training (PKM). Meanwhile, at the final coaching stage, the star communication pattern is applied in the accountability report activity. These results indicate a dynamic adaptation of communication patterns according to the needs and objectives of each stage of the student organization development.